PEMBERDAYAAN ANGGOTA KOPERASI SIMPAN PINJAM - Kaja, Kaja (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Savings and Loan Cooperatives (SLC) play a significant role in increasing the economic income of communities as part of their mission to elevate people's livelihoods and eradicate poverty. The development of cooperatives focuses on improving member welfare based on the principles of by the members, for the members, and from the members. Member empowerment is carried out through education and training, which serve as one of the prerequisites for cooperative membership. Members are obligated to deposit funds in the form of share savings, which consist of principal and mandatory savings. Principal savings are made once during membership, while mandatory savings are paid monthly, with the amount determined through the Annual Members' Meeting. Additionally, cooperatives offer voluntary savings as non-share savings with an interest rate of 14% per year. Share savings cannot be withdrawn if they are being used as loan collateral, and they can only be withdrawn by the owner or through a proxy with a notarized power of attorney.The empowerment program encompasses various aspects of individual development, including increasing knowledge, skills, entrepreneurship, welfare, and moral responsibility, particularly in loan repayment. This study aims to analyze the empowerment and development of savings and loan cooperatives. The research employs a descriptive method with data collected through interviews and observations.The results show that empowering members of savings and loan cooperatives through education, training, and motivation can enhance their independence in improving their economy and income.